LOOK AT THE TREATMENT OF ATOPIC DERMATITIS AS AN AUTOIMMUNE SKIN PROCESS - Tolibov M.M. (PEDAGOGS, 2024)
Annatation: this article attempts to reveal the main reasons for the effectiveness and safety of the use of comfodermK cream (methylprednisolone aceponate 0.1%) and tacropic ointment 0.03% (tacrolimus 0.03%) for the treatment of manifestations of atopic dermatitis on the face. To carry out scientific work, the author evaluated the results of treatment was carried out in 12 patients, aged 6 to 13 years, with a diagnosis of atopic dermatitis, the childhood period was moderate. The problem in question is still little studied, therefore, requires more thorough research.